2019
DOI: 10.1210/jc.2019-00143
|View full text |Cite
|
Sign up to set email alerts
|

PTH Modulation by Aldosterone and Angiotensin II is Blunted in Hyperaldosteronism and Rescued by Adrenalectomy

Abstract: Context Accumulating evidence suggests a link between adrenocortical zona glomerulosa and parathyroid gland through mechanisms that remain unexplored. Objectives To test the hypothesis that in vivo angiotensin II blockade affects PTH secretion in patients with hypertension and that aldosterone and angiotensim II directly stimulate PTH secretion ex vivo. Design and Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
1
31
0
1
Order By: Relevance
“…Brown et al could demonstrate a 2-to 4-fold increase of mineralocorticoid and angiotensin II type 1 receptors in adenomatous tissue of the parathyroid gland [19]. A recent study of Lenzini et al in primary culture of human parathyroid cells showed that both aldosterone and angiotensin II increased PTH secretion, by acting through MR and angiotensin II type 1 receptors, respectively [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brown et al could demonstrate a 2-to 4-fold increase of mineralocorticoid and angiotensin II type 1 receptors in adenomatous tissue of the parathyroid gland [19]. A recent study of Lenzini et al in primary culture of human parathyroid cells showed that both aldosterone and angiotensin II increased PTH secretion, by acting through MR and angiotensin II type 1 receptors, respectively [8].…”
Section: Discussionmentioning
confidence: 99%
“…with normal aldosterone levels demonstrated that six weeks of treatment with the mineralocorticoid receptor antagonist spironolactone resulted in a relative decrease in PTH compared to placebo [19]. Recently, the study of Lenzini et al showed that the inhibition of angiotensin II with captopril lowered PTH levels both in essential hypertension and in APA patients after adrenalectomy [8]. Interestingly, captopril had no effect on the elevated PTH levels in PA patients, suggesting that the parathyroid gland loses its ability to respond to acute angiotensin II inhibition when hyperaldosteronism coexists with hyperparathyroidism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the RAAS and PTH is significantly positive, as patients with PA exhibit higher PTH levels compared to secondary aldosteronism and primary hypertension patients (2,17,77). Recent studies have suggested that mild hyperparathyroidism is a characteristic of PA (80), irrespective of the subtype of PA (81). Furthermore, PA may even contribute to secondary hyperparathyroidism (77).…”
Section: Effects Of Raas Biomarker Levels On Pth Levels How Does the mentioning
confidence: 99%
“…Aldosteronoma resection decreases the PTH level (83). Adrenalectomy not only cures hyperaldosteronism but also corrects hyperparathyroidism (17,80). Compared with MRA, surgical treatment reduces PTH levels more obviously in PA patients (77).…”
Section: Changes In Pth After the Inhibition Of Raas Functionmentioning
confidence: 99%